PENERAPAN GOOD GOVERNANCE DI KECAMATAN MARPOYAN DAMAI KOTA PEKANBARU (Studi Kasus Pada Pelayanan Pertanahan) - Munaf, Yusri; Febrian, Ranggi Ade; S, Rizky Setiawan (UIR PRESS, 2018)
Implementation of good governance is an absolute necessity in the administration of government including the district government. Kecamatan as a Local Device has a very strategic role as the spearhead of service and barometer of Public service delivery. Locus research in Sub Marpoyan Damai Pekanbaru with focus on land service. Using three dimensions of good governance implementation developed by B.C. Smith (2007) includes accountability, transparency, and legal certainty as a knife analysis to look at empirical problems. The research method used is qualitative research. Based on research in the field can be concluded that the implementation of good governance in the service of land in the District Marpoyan Damai Pekanbaru City still not done well. This can be seen from the dimensions of accountability are still found weaknesses are uncertainty of service time, lack of discipline of employees, and still found injustice treatment between the general public with family or employee acquaintances. The transparency dimension is found in the field of some weaknesses among others the weakness of the disclosure of the availability of information to the public, this is due to the supporting facilities such as information boards, SOP flow, and the high volume of land service management in Marpoyan Damai District Office recorded in 2015 to 2016 640 letter. Even the Sub-district stated that they need training because the limited number of employees who understand the land rules is also a problem. While the dimensions of the rule of law are quite good, it's just that the problems come from people who do not understand SOPs and regulations related to land.